Cordycepin ameliorates diabetic nephropathy injury by activating the SLC7A11/GPX4 pathway - Bing Wu; Jing Wang; Xiaohui Yan; Gang Jin; Qiong Wang (Journal of Diabetes Investigation)
ABSTRACT Background Cordycepin (CRD) has been identified to alleviate diabetes‐induced injuries and complications including diabetic nephropathy (DN). Here, this work focused on probing the specific effects and potential mechanisms of CRD on DN progression. Methods High glucose (HG)‐induced mouse podocyte cell line (MPC5) was used for in vitro functional analyses. Cell proliferation and apoptosis were determined using cell counting kit‐8 assay, 5‐ethynyl‐2′‐deoxyuridine assay, and flow cytometry, respectively. ELISA analysis detected inflammatory factors. Cell ferroptosis was assessed by measuring the levels of Fe2+, glutathione, reactive oxygen species, and malonaldehyde. Results CRD treatment suppressed HG‐induced apoptosis, inflammation, and ferroptosis in podocytes. CRD treatment elevated SLC7A11 and GPX4 expression in HG‐treated podocytes. The overexpression of SLC7A11 or GPX4 suppressed HG‐evoked apoptosis, inflammation, and ferroptosis in podocytes. Moreover, the silencing of SLC7A11 or GPX4 abolished the protective effects of CRD on HG‐treated podocytes. Moreover, CRD ameliorated renal structure injury and inflammation in STZ‐induced diabetic mice by modulating SLC7A11 or GPX4 expression. Conclusions Cordycepin suppressed HG‐induced apoptosis, inflammation, and ferroptosis in podocytes in vitro, and ameliorated renal injury and inflammation in STZ‐induced diabetic mice by activating the SLC7A11/GPX4 pathway.